(untitled) (World Bulletin of Management and Law, 2022)
In this article, labor resources, their formation and economic role are theoretically investigated. And also, the difference between labor resources, based on their specific features, is justified. The current state of the use of labor resources in Uzbekistan is analyzed and economically justified proposals and recommendations are developed for their effective use in the future